Comparison of the Nomenclatures of Herbal Substances Used in the Russian and Foreign Pharmacopoeial Texts - L. N. Frolova; E. L. Kovaleva; E. I. Sakanyan; V. Yu. Kuteynikov; V. V. Shelestova; M. A. Cheremisina (Регуляторные исследования и экспертиза лекарственных средств, 2020)
The study of the nomenclature of officinal herbal substances and medicinal plants is important for finding potential ways of expanding the existing range of raw materials used in the production of herbal medicinal products. The authors compared the standards included into the State Pharmacopoeia of the Russian Federation, national pharmacopoeias of the Member States of the Eurasian Economic Union, and the world’s leading pharmacopoeias with a focus on herbal substances, medicinal plants, morphological groups of herbal substances, and the proportion of cultivated medicinal plants versus wild medicinal plants. The paper describes historical changes in the nomenclature of herbal substances included in various editions of the Russian Pharmacopoeia. The analysis of the State Register of Medicinal Products revealed the most common morphological groups of herbal substances used in Russia for the production of herbal medicinal products. The paper provides information about the largest Russian manufacturers of herbal medicinal products that preserve national traditions and develop new dosage forms. It outlines ways of improving standardisation of herbal substances using current test methods for characterisation of biologically active substances. The analysis helped to identify potential ways of expanding the range of herbal raw materials: the use of botanical species closely related to officinal ones, increasing the number of morphological groups of substances by integrated use of harvested plants, the inclusion of non-officinal botanical species that have a long history of use in the traditional medicine into the Russian list of officinal species.